2021
DOI: 10.1007/s00259-021-05303-5
|View full text |Cite|
|
Sign up to set email alerts
|

[18F]FDG PET radiomics to predict disease-free survival in cervical cancer: a multi-scanner/center study with external validation

Abstract: Purpose To test the performances of native and tumour to liver ratio (TLR) radiomic features extracted from pre-treatment 2-[18F] fluoro-2-deoxy-D-glucose ([18F]FDG) PET/CT and combined with machine learning (ML) for predicting cancer recurrence in patients with locally advanced cervical cancer (LACC). Methods One hundred fifty-eight patients with LACC from multiple centers were retrospectively included in the study. Tumours were segmented using the Fuzzy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 61 publications
(94 reference statements)
2
37
0
Order By: Relevance
“…We cannot confirm that all FDG-avid LNs are histopathological lymphadenopathies. Finally, recently there are many promising methods such as radiomics, machine learning, and especially deep learning ( 34 , 35 ). Combining these promising image analysis techniques may have more significant predictive values for the prognosis of cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…We cannot confirm that all FDG-avid LNs are histopathological lymphadenopathies. Finally, recently there are many promising methods such as radiomics, machine learning, and especially deep learning ( 34 , 35 ). Combining these promising image analysis techniques may have more significant predictive values for the prognosis of cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Supplementary Table S9, ComBat improved the AUC and C-index in all intra_tumoral CT models compared to that without ComBat except for the AUC of OS prediction, while the improvement in intra_tumoral PET model is not obvious. As shown in Figure 5, first two principal component of principal component analysis (PCA) were plotted, before ComBat, three batches are totally separable in both PET and CT, after ComBat, three batches get closer and inseparable in CT, while still separable in PET, this probably limit the performance of ComBat in PET models [45][46]. Exploring other more effective harmonization methods should be investigated in the future, besides, proper batch division based on the factor that most contribute to batch effect should also be investigated.…”
Section: Figure 4 (A-c) Receiver Operating Characteristic Curves (Roc) Comparison Of Selected Models As Listed In Table 3 (D-f) Kaplan-mementioning
confidence: 99%
“…We extracted two hundred and fteen features from the segmented volumes, which included rst order grey level statistics, geometry, fractals, texture matrix based features and others. Features were extracted using the Oncoradiomics research toolbox and their detailed description can be found in supplementary data of our previous study [23]. All features were calculated according to the Imaging biomarkers standardization initiative (IBSI) [25].…”
Section: Images Radiomic Featuresmentioning
confidence: 99%
“…PET/CT studies were performed in the CHU of Liège, where 89 studies were acquired using a Philips Gemini TF or BB (scanner A), in the CHU of Brest and ICO St Herblain, where 17 and 34, respectively, were acquired using a Siemens Biograph mCT (scanner B) and at the McGill University Health Center, where 18 studies were performed with a General Electric Discovery ST (scanner C). The patient's clinical characteristics, treatment, acquisition and reconstruction protocols are described in our previous study [23].…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation